Faktor-Faktor Yang Berhubungan Dengan Pengetahuan Perawat Tentang Penatalaksanaan Asuhan Keperawatan Pasien Dekompensasi Kordis Di Ruang ICVCU RSUD Dr.MOEWARDI - Widodo Widodo ((JKG) Jurnal Keperawatan Global, 2016)
Abstract : Knowledge, Management, Nursing Care Application Of Cardiac Decompensation. This study is a non-experimental quantitative research using correlation descriptive method. Research subjects are nurses who provide nursing care in patients with cardiac decompensation. There are 22 people as respondents. the form of data collection is using questionnaire. The Data analysis techniques using the Rank Spearman.The results show the value of the bivariate analysis Rank Spearman formula that there is no correlation between nurse’s age with the nurse's knowledge about the management of the nursing care of patients with cardiac decompensation, shown as calculated values of rcount < rtable (0, 082 <.428). there is no correlation between level of a nurse's knowledge education about management of the nursing care of patient with cardiac decompensation shown as calculated values of rcount < rtable (0.290 < 0.428), there is no correlation between the long time of nurse working with the nurse’s knowledge about the management of nursing care of patients with cardiac decompentation, shown as the value of rcount < rtable (0.245 < 0.428), and there is a correlation between training program with the knowledge of nurse on the management of the of the patients nursing care with cardiac decompensation which is counted rcount < rtable (0.542> 0.428). There is a correlation between training factor with the nurses knowledge about nursing care management of patients with cardiac decompensation